HUBUNGAN GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA TENAGA KESEHATAN DI PUSKESMAS KOTA WILAYAH UTARA KEDIRI - Reny Nugraheni; Eko Cahyo Saputro, Amiruddin (Jurnal Kesehatan, 2024)
Health services really need optimal service, then health agencies are required to have a good performance. In an increase of a good performance required paramedics who having a good performance , but in improving the performance of health workers required approach , and that could be done by one of them is by the approach of the style of leadership. Besides leadership styles factors motivation work health workers can affect performance health workers. This study to knowledge of the leadership style as well as the relations leadership stylesand motivation with the performance of health workers. The methodology that was used is the cross sectional by using respondents were a total of 43 . Population research that all health workers, research locations in public health Kota Wilayah Utara Kediri. Statistical tests that is used pt pgn promised to supply the test and been approved Somers’d to gain an understanding the leadership styles and motivation with the performance of health workers . This research result indicates the leadership instructions , consultation participation , delegates get the percentage the highest leadership stylesconsultation 67.44 %. Work motivation in the category of very good 60.47 % .The performance of health workers in the category of very good 90.70 % , of the Statistical tests received a value of 0.096 and 0.034 less than 0.05 so said there was a correlation between leadership styleswith the performance of health workers , there was a correlation between motivation to performance health workers. leadership styles consultation could be recommendations the style of leadership in the field of health services , leader must to motivate your health workers to increase the performance of health workers.